Playing With Uncertainty: Facilitating Community-Based Resilience Building - Avendano-Uribe, Bryann (2022)
Resilience has become a fundamental paradigm for communities to deal with disaster planning. Formal methods are used to prioritise and decide about investments for resilience. Strategies and behaviour need to be developed that cannot be based on formal modelling only because the human element needs to be incorporated to build community resilience. Participatory modelling and gaming are methodological approaches that are based on realistic data and address human behaviour. These approaches enable stakeholders to develop, adjust, and learn from interactive models and use this experience to inform their decision-making. In our contribution, we explore which physical and digital elements from serious games can be used to design a participatory approach in community engagement and decision-making. Our ongoing research aims to bring multiple stakeholders together to understand, model, and decide on the trade-offs and tensions between social and infrastructure investments toward community resilience building. Initial observations allow us as researchers to systematically document the benefits and pitfalls of a game-based approach. We will continue to develop a participatory modelling exercise for resilience planning with university graduate students and resilience experts within academia in Christchurch, New Zealand.